The Influence of Instagram Social Media on Consumer Buying Interest at the Nyonya Fashion store, South Bengkulu - Dian Lova Setiana; Karona Cahya Susena; Zahrah Indah Ferina (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
Effort done/conducted to conduct`product marketing or service by using media of internet can be referred as also marketing internet. Marketing Internet [is] marketing side of commerce elektornic, what consist of job/activity of company to communicate something, promoting, and selling service and goods [pass/through] internet. Target of this research To know influence of social media of instagram to enthusiasm buy consumer in Shop Lady of Fashion Bengkulu South south. this Research type is research of field that is measuring value one or more variable in sampel. All data represent reflection an measured variable according to its classification. Data personate input to be processed is clear, [is] later;then analysed and yield output for the determination of furthermore plan. Sampel in this research is cutomer/ client of Lady shop of Fashion Bengkulu south amounting to 95 people. Result of Analysis linear regression of bergaanda the is Y = 7,486 + 0,825 X1, this matter depict direction of regresi which are positive, its meaning of Social Media variable of Instagram ( X) there are positive influence to Enthusiasm buy consumer ( Y) in Shop Lady of Fashion Bengkulu south. Level of coefficient value of determinasi from result of enumeration by using SPSS can know by coefficient value of determinasi of R square equal to 0,721. Matter this means that Social Media value of Instagram ( X) have an effect on to Enthusiasm buy consumer ( Y) equal to 72,1% while the rest 27,9 % influenced by other variable which do not check in research. Result of test of t [at] level of signifikansi 0,05 explaining that by partial Social Media of Instagram have influence which is signifikan to Enthusiasm buy consumer [in] Shop Lady of Fashion Bengkulu south.